A high-order absorbing boundary condition for scalar wave propagation simulation in viscoelastic multilayered medium. Issue 6 (21st December 2020) - Wu, Lihua; Zhao, Mi; Du, Xiuli
Abstract : Purpose: The finite element method (FEM) is used to calculate the two-dimensional anti-plane dynamic response of structure embedded in D'Alembert viscoelastic multilayered soil on the rigid bedrock. This paper aims to research a time-domain absorbing boundary condition (ABC), which should be imposed on the truncation boundary of the finite domain to represent the dynamic interaction between the truncated infinite domain and the finite domain. Design/methodology/approach: A high-order ABC for scalar wave propagation in the D'Alembert viscoelastic multilayered media is proposed. A new operator separation method and the mode reduction are adopted to construct the time-domain ABC. Findings: The derivation of the ABC is accurate for the single layer but less accurate for the multilayer. To achieve high accuracy, therefore, the distance from the truncation boundary to the region of interest can be zero for the single layer but need to be about 0.5 times of the total layer height of the infinite domain for the multilayer. Both single-layered and multilayered numerical examples verify that the accuracy of the ABC is almost the same for both cases of only using the modal number excited by dynamic load and using the full modal number of infinite domain. Using the ABC with reduced modes can not only reduce the computation cost but also be more friendly to the stability. Numerical examples demonstrate the superior properties of the proposed ABC with stability, high accuracy and remarkable coupling with the FEM. Originality/value: A high-order time-domain ABC for scalar wave propagation in the D'Alembert viscoelastic multilayered media is proposed. The proposed ABC is suitable for both linear elastic and D'Alembert viscoelastic media, and it can be coupled seamlessly with the FEM. A new operator separation method combining mode reduction is presented with better stability than the existing methods.